Evaluation of cytologic and biochemical variables in blood, plasma, and peritoneal fluid from calves before and after umbilical herniorrhaphy - Peiró, Juliana Regina [UNESP]; Lucato, Beatriz [UNESP]; Mendes, Luiz C. N. [UNESP]; Ciarlini, Paulo Cesar [UNESP]; Feitosa, Francisco Leydson Formiga [UNESP]; Bonello, Fabio L. [UNESP]; Maemura, Silvana M. [UNESP]; Soares, Gisele T. [UNESP]; Santana, Aureo E. [UNESP]; Perri, Silvia Helena Venturoli [UNESP] (Amer Veterinary Medical Assoc, 2009)
Objective-To establish reference intervals for cytologic and biochemical variables in peritoneal fluid, whole blood, and plasma in calves with congenital umbilical hernias (CUHs) before and after herniorrhaphy and to assess whether those variables in calves with CUHs were altered, compared with findings in clinically normal calves.Animals-20 Holstein calves with or without a CUH.Procedures-10 calves with CUHs underwent herniorrhaphy. Blood and peritoneal fluid samples from all 20 calves were collected for cytologic and biochemical analyses on days 0 (before surgery), 1, 3, 5, 7, and 15. Data from the 2 groups were compared.Results-Reference intervals for the variables of interest were established for each group, Before surgery, calves with CUHs had significantly greater plasma total protein concentration and creatine kinase (CK) and aspartate aminotransferase activities and peritoneal fluid specific gravity values, compared with values for calves without CUHs. At various time points after surgery, peritoneal fluid total protein concentration; fibrinogen concentration; nucleated cell, polymorphonuclear cell, and lymphocyte counts; specific gravity; and lactate dehydrogenase, aspartate aminotransferase, and CK activities in calves with CUHs were significantly different from values in calves without CUHs. Some plasma and blood variables leg, total protein concentration, neutrophil count, and CK activity were significantly different between the 2 groups.Conclusions and Clinical Relevance-Values of certain cytologic and biochemical variables in peritoneal fluid, blood, and plasma were different between calves with and without CUHs. Thus, determination of reference intervals for these variables is important for interpreting diagnostic test results in calves with CUHs. (Am J Vet Res 2009;70:423-432)